Development of an Integrated Subspecialist Multidisciplinary Neuro-oncology Service. Issue 1 (21st August 2013) - Price, Stephen J; Guilfoyle, Mathew; J Jefferies, Sarah; Harris, Fiona; Oberg, Ingela; G Burnet, Neil; Santarius, Thomas; Watts, Colin
Abstract: Traditionally, the poor outcome for patients with malignant brain tumours led to therapeutic nihilism. In turn, this resulted in lack of interest in neurosurgical oncology subspecialisation, and less than ideal patient pathways. One problem of concern was the low rate of tumour resection. Between 1997 and 2006, 685 treated glioblastomas were identified. In the first four years only 40% of patients underwent tumour resection, rising to 55% in the last four years. Before revision of the pathway, the median length of hospital stay was 8 days, and 35% of patients received the results of their histology outside of a clinic setting. A pathway of care was established, in which all patients were discussed pre-operatively in an MDT meeting and then directed into a new surgical neuro-oncology clinic providing first point of contact. This limited the number of surgeons operating on adult glioma patients and aided recruitment into research studies. Now, three consultant neurosurgeons run this service, easily fulfilling IOG requirement to spend >50% of programmed activities in neuro-oncology. Nursing support has been critical to provide an integrated service. This model has allowed increased recruitment to clinical trials. The introduction of this service led to an increase in patients discussed pre-operatively in an MDT (66% rising to 87%; P=0.027), an increase in the rate of surgical resection (from 40% to 80%) and more patients being admitted electively (from 25% to 80%; P<0.001). There was a reduction in the median length of stay (8 days reduced to 4.5 days; P<0.001). For the cohort of GBM patients that went on to have chemoradiotherapy we improved median survival to 18 months, with 35% of patients alive at two years, comparable to international outcomes. Implementing a specialist neurosurgical oncology service begins with understanding the patient care pathway. Our patients have benefitted from the culture of subspecialisation and the excellent inter-disciplinary working relationships that have been developed.